Gravobraduras: processos de impressão e objetos de estrutura dobrada - Ávila, Eduardo Araújo de (2014)
This work presents the outcomes of a research master’s degree in Art and Visual Culture, which consists of experiments in printmaking and in studies on the use of foldings as matrices, whose poetic concept is defined as “gravobraduras”. The study has as reference the wrapping culture (tsutsumu bunka), which involves not only the study of origami, but also about other practices, such as furoshiki, that include the production of involucres and wrappings. The reference in question alludes to “practice of Japanese gift” and the artistic production of this work to the “wanderings of Japanese immigrants in Brazil”. Therefore, the primary objective of this research is to analyze what are the paths, sometimes errant sometimes constant, in which the image generated by the “matrix folding” travels up to become a visual pattern, but also evaluate the development of the artistic production in three methods of printing: by high relief (matrix folding), by permeation (silkscreen) and by digital means. The research also involves reflections on artistic creation as creating networks, according to Cecilia Salles, who emphasizes that are important the concomitant actions and the establishment of links between relevant subjects to the research to generate its own methodology and poetic.